2015
DOI: 10.1007/s11162-015-9388-5
|View full text |Cite
|
Sign up to set email alerts
|

Does Holding a Postdoctoral Position Bring Benefits for Advancing to Academia?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 29 publications
0
28
0
1
Order By: Relevance
“…In particular, surveys of postdocs in the U.S. and Mexico have shown that postdoc training is considered to enhance their research profile [2], [14] and to increase their chance of attaining a tenure track faculty position [8]. On the other hand, some studies have indicated that postdoc positions are taken when no other employment options are available [10].…”
Section: Reasons For Postdoc Trainingmentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, surveys of postdocs in the U.S. and Mexico have shown that postdoc training is considered to enhance their research profile [2], [14] and to increase their chance of attaining a tenure track faculty position [8]. On the other hand, some studies have indicated that postdoc positions are taken when no other employment options are available [10].…”
Section: Reasons For Postdoc Trainingmentioning
confidence: 99%
“…This association is particularly strong among women [16]- [18]. Age at the time of PhD attainment tends to have a negative correlation with postdoc training, which has been attributed to shorter expected career span and/or family obligations for older PhDs [2], [9], [10]. Moreover, Lin and Chiu found that longer expected time of PhD degree completion is associated with higher likelihood of postdoc employment, possibly due to relatively fewer job options being available [10].…”
Section: Characteristics Of Postdoc Participantsmentioning
confidence: 99%
See 3 more Smart Citations